How Livestream Interactivity Drives Repurchase Intention in Social Commerce: The Mediating Role of Trust - Viona Joycelyn; Auditia Setiobudi (Journal of Accounting and Finance Management, 2026)
TikTok Shop has swiftly advanced social commerce via live shopping, where immediate engagement can influence consumer loyalty. Nevertheless, empirical evidence regarding the translation of live-stream involvement into repurchase intention is scarce in regions with high digital penetration, such as Bali.  This research investigates the impact of TikTok Live Interactivity on Repurchase Intention, with Live Streaming Trust serving as a mediating factor among TikTok Shop users in Bali. A quantitative explanatory approach was employed utilizing purposive sampling of 234 eligible TikTok Shop users from five principal regions in Bali: Badung, East Denpasar, Singaraja, West Denpasar, and Kuta. Data were gathered by a structured questionnaire comprising 18 reflective indicators across three categories and analyzed with SEM-PLS (SmartPLS 4) with bootstrapping (5,000 resamples). The findings indicate that TikTok Live Interactivity significantly elevates Live Streaming Trust (β = 0.804) and directly improves Repurchase Intention (β = 0.431).  Live Streaming Trust significantly influences Repurchase Intention (β = 0.476) and partially mediates the association between interactivity and repurchase (indirect β = 0.383). The model exhibits significant explanatory capability (R² = 0.646 for trust; R² = 0.743 for repurchase intention). These findings emphasize that interactive live features must be combined with intentional trust-building tactics to optimize recurring transactions, providing practical recommendations for merchants and platform designers to enhance retention strategies in TikTok Live commerce.